Dietary arginine silicate inositol complex inhibits periodontal tissue loss in rats with ligature-induced periodontitis - Dundar, Serkan; Eltas, Abubekir; Hakki, Ema S.; Malkoc, Siddik; Uslu, M. Ozay; Tuzcu, Mehmet; Şahin, Kazım (Dove Medical Press Ltd, 2016)
The purpose of this study was to induce experimental periodontitis in rats previously fed diets containing arginine silicate inositol (ASI) complex and examine the biochemical, immunological, and radiological effects. Fifty two 8-week-old female Sprague Dawley rats were equally divided into four groups. The control group included those fed a standard rat diet with no operation performed during the experiment. The periodontitis, ASI I, and ASI II groups were subjected to experimental periodontitis induction for 11 days after being fed a standard rat diet alone, a diet containing 1.81 g/kg ASI complex, or a diet containing 3.62 g/kg ASI complex, respectively, for 8 weeks. Throughout the 11-day duration of periodontitis induction, all rats were fed standard feed. The rats were euthanized on the eleventh day, and their tissue and blood samples were collected. In the periodontitis group, elevated tissue destruction parameters and reduced tissue formation parameters were found, as compared to the ASI groups. Levels of enzymes, cytokines, and mediators associated with periodontal tissue destruction were lower in rats fed a diet containing ASI complex after experimental periodontitis. These results indicate that ASI complex could be an alternative agent for host modulation.
Keywords: arginine silicate inositol complex; experimental periodontitis; host modulation; micro-computed tomography; periodontal infection